CRYSTAL MORPHOLOGY OF DIAMONDS FROM RUTILE-SPHENE ECLOGITE - Safronov P.P.; Tugovik G.I.; Kirasirova V.I. (My University, 1987)
The authors analyzed diamonds from rutile-sphene eclogite bodies whose garnet is not pyrope, but andradite, and which lack omphacite pyroxene. These eclogite bodies occur within local ring structures, revealed by remote sensing in an area of Archean granulites. Eclogite diamonds were 0.5 to 0.6 nm in diameter. They are represented by the fragment of a pure blue-white crystal and by a well-faceted tetrahexahedron, also without visible impurities but with a dull greenish surface. Both crystals, are relatively high in nitrogen in the form of two substituting atoms (5.1018 + 5.1019 cm-3) and, therefore, differ from synthetic diamonds and from diamonds in rocks of eclogite-gneiss complexes, whose origin is assumed to be metamorphic. Analogs the diamonds with these properties are found in kimberlite pipes.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей